Keberhasilan Konseling Kelompok Teknik Manajemen Diri untuk Mereduksi Prokrastinasi Akademik Siswa SMP - Farah Tiana Dhion; Wahyu Nanda Eka Saputra; Nur Handayani (Universitas Sebelas Maret, 2022)
Abstract: This study aims to determine the implementation of group counseling through self-management techniques that can reduce student academic procrastination in junior high school students. The background that underlies this research is because many students still do academic procrastination so it also has an impact on their learning process. The type of research used is guidance and counseling action research through pre-action and 2 cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. Data collection techniques are in the form of questionnaires, observations, and interviews. The results of the pre-action research obtained an average of 74.2 then given the action in the first cycle obtained an average score of 63.8. In cycle II it decreased with an average score of 54.8 whereas in this cycle 5 subjects were not in the high category. This study concludes that group counseling self-management techniques can be used as an alternative to reducing academic procrastination behavior.